Investigation of anticancer compounds from non-infected agarwood branch towards development of breast cancer therapeutics - Phirdaous Abbas (Kulliyyah of Engineering, International Islamic University Malaysia, 2022)
Agarwood; a dark-aromatic resinous substance released by Aquilaria trees upon infection; is one of the most treasured forest valuable resources. The plant materials from the trees were also reported to be utilized traditionally across various communities to fulfil religious, medicinal, and aromatic preparations. There has also been an increase of modern ethnomedicinal reports of agarwood or its plant materials towards various diseases. While a lot of focus has been on the resin itself, less has been focused on the agarwood non-infected branch which is abundant all year round and mostly considered as a waste from agarwood plantation. Our previous work done on Aquilaria subintegra non-infected branch has demonstrated profound growth inhibitory effects against Michigan Cancer Foundation-7 (MCF-7) breast cancer cells. Thus, the current study attempted to investigate the underlying cell death mechanisms behind the agarwood branch ethanolic extract (ABEE) against MCF-7 cells as well as enhance the extraction process conditions via one factor at a time analysis (OFAT) and Response Surface Methodology (RSM)-based experimental design; employing the Faced Centered Central Composite Design (FCCCD). The study also employed a bio-guided approach in an attempt to isolate and identify potential active compounds using column chromatography, thin layer chromatography, Gas Chromatography Mass Spectroscopy (GCMS), Fourier Transformed Infrared Spectroscopy (FTIR), Proton (H-NMR) and Carbon-13 (C-NMR) Nuclear Magnetic Resonance Spectroscopy, Ultraviolet-visible spectroscopy (UV) and Liquid Chromatography Mass Spectroscopy (LCMS). The study first replicated the established extraction process conditions to obtain the extract, which was then subjected to flow cytometry analysis and gene expression profiling with pathway analysis via real time Human Cell Death PathwayFinder™ RT2 Profiler PCR array. It was observed that the extract caused time-dependent apoptosis-necrosis of MCF-7 cells and significantly affected 48 genes (41 down-regulated and 7 up-regulated genes) indicative of cellular responses towards stimuli of specific apoptotic signals. NF-KB1 gene was the most down-regulated gene (fold change of -26.704) and TRAF2 gene was the most up-regulated gene (fold change of 5.52). Pathway analysis conducted using online KEGG tool suggested that these differentially expressed genes (DEGs) regulated cell death mechanisms via the apoptosis and p53 signalling pathways. Then, through combination of OFAT and FCCCD; an optimal extraction process employing the temperature and solid-liquid ratio at 45 °C and 1:19 (w/v), respectively, with desirable factors; (ⅰ) safe temperature (less risk towards thermos-labile compounds) and (ⅱ) economical solvent volume, was obtained. The model predicted ABEE yield of 30.232 ± 0.266 mg/g dried materials (DM) and validation run afforded ABEE at 25.35 ± 1.19 mg/g DM (p-value = 0.007). ABEE obtained from the recommended process conditions showed cytotoxicity effects on MCF-7 cells with IC50 estimate of 3.645 ± 0.099 µg/mL. The extract also affected MCF-7 cell attachment and viability with altered morphology. Th bio-guided approach of fractionation and isolation process then led to a plethora of fractions. However, decrease of cytotoxicity was observed after each phase of fractionation suggesting synergism-dependent effect (of the crude extract) which became more apparent towards the end of the fractionation study. Nonetheless, the study isolated and identified a non-active orange-yellow needle-like crystal flavonoid, ABEE-FR4A1; characterized to be 5-hydroxy-7,4ʹ-dimethoxyflavone (13.7 mg, 6.13 % w/w). The parent fraction (FR 2-3, 2037 mg) and subfraction (FR 3A3, 223.5 mg) exhibited moderate cytotoxic effects (28.52 ± 0.1524 and 23.11 ± 0.1141 µg/mL), but inferior to the crude extract. In conclusion, the study had determined the underlying cell death mechanisms of ABEE against MCF-7 cells, optimized the extraction process conditions and identified several compounds with varying cytotoxic effects. These finding would add value to the non-infected agarwood branch that is abundant in agarwood plantations thus help promote the sustainable growth of agarwood industry; and pave the way towards development of locally sourced natural anti-cancer therapeutics.